Parental burnout and resilience intervention among Chinese parents during the COVID-19 pandemic - Liu, Yixiao; Chee, Jing Han; Wang, Ying (Frontiers in Psychology, 2022)
Parental burnout is a mental state that combines long-term stress and depression with an overwhelming feeling of parental pressure. In Study 1, we conducted a web-based survey of 390 Chinese parents (75.1% mothers) with children aged 1-18 years old (Mean age = 9.05 years, SD = 5.098) to examine the parental burnout during the COVID-19 global pandemic and to identify associated factors during the national lockdown. In Study 2, eight weeks of resilience intervention was administered to 20 parents to compare parental resilience and parental burnout before and after the intervention. The correlational study showed that greater parental burnout occurred in parents with the lower educational levels and in parents of school-age children. The risk factors that of parental burnout included household burden, children’s interference with work; protective factors included living materials, family atmosphere, and parent-child meeting frequency. The intervention study showed the effectiveness of meditation intervention in resilience and parental burnout, suggesting that meditation training can effectively increase parental resilience and reduce parental burnout. These findings demonstrate the risk and protective factors associated with parental burnout during the COVID-19 lockdown and highlight the positive role of meditation in mitigating parental burnout.